Penerapan Model Think Talk Write Berbantuan Leaflet Sintaksis Upaya Peningkatan Penalaran Kritis dan Keterampilan Menulis Kata Acak Siswa Kelas Rendah - Firdaus, Redzuan Adam; Purwati, Panca Dewi (YASIN, 2025)
The low levels of critical reasoning and writing skills among primary school students in Indonesian language instruction are often attributed to the predominance of conventional teaching methods that fail to foster reflective thinking and written expression. This study aims to describe the implementation of leaflet-based teaching materials grounded in the Think–Talk–Write (TTW) model and to analyze their effectiveness in enhancing students’ critical reasoning attitudes and scrambled-word writing skills. A mixed methods approach with a Sequential Explanatory design was employed, involving 28 third-grade students at SD Negeri Mangkang Wetan 02. Data were collected through classroom observation, writing tests, and interviews, and analyzed using a paired sample t-test and the interactive analysis model of Miles and Huberman. The results show a significant improvement in students’ critical reasoning attitudes, with 82% achieving ratings in the good to very good categories, and an increase in average writing scores from 67.5 to 85.7 (N-Gain = 0.56; moderate category). The implementation of the TTW model supported by leaflet materials fostered an active, reflective, and collaborative learning environment that encouraged logical thinking and systematic writing. These findings demonstrate that TTW-based leaflet instructional materials are effective in strengthening literacy and higher-order thinking skills in Indonesian language learning at the primary school level.